Gemcitabine‐cisplatin versus gemcitabine‐oxaliplatin doublet chemotherapy in advanced gallbladder cancers: a match pair analysis. (11th April 2017) - Ramaswamy, Anant; Ostwal, Vikas; Pinninti, Rakesh; Kannan, Sadhana; Bhargava, Prabhat; Nashikkar, Chaitali; Mirani, Jimmy; Banavali, Shripad
Abstract: Background: Gemcitabine‐cisplatin (GC) and gemcitabine‐oxaliplatin (GO) are the most commonly used regimens in advanced gallbladder cancer (GBC). Methods: The data of patients with advanced GBC, treated between January 2013 and June 2015 were retrieved. A 1:1 matching without replacement was performed by using nearest neighbor matching method. Results: A total of 326 patients (163 GC and 163 GO), were matched 1:1 by age and gender. The response rates for GC and GO were 31.2% and 36.3% ( P = 0.350). The overall median event free survival (EFS) was 4.34 months (95% CI 4.030–4.644 months). The median EFS was 4.67 months (95% CI 4.060–5.271 months) in GC cohort and 3.88 months (95% CI 3.369–4.385 months) in GO cohort ( P = 0.023). The overall median OS was 8.016 months (95% CI 7.361–8.672 months). The median OS was 8.02 months (95% CI 7.257–8.776 months) in GC cohort and 7.79 months (95% CI 6.690–8.88 months) in GO cohort ( P = 0.455). The incidence of Grade 2/3 peripheral neuropathy (9.2% vs. 3.1%; P = 0.445) and Grade 3/4 transamintis (14.7% vs. 6.1%) was higher with GO while the incidence of anemia (22.1% vs. 6.7%; P < 0.001), neutropenia (7.3% vs. 2.4%; P = 0.49) and thrombocytopenia (9.8% vs. 3.7%; P = 0.033) was higher with GC. Conclusion: Gemcitabine‐cisplatin or gemcitabine‐oxaliplatin can be used as an initial regimen in advanced GBC. Higher EFS, potentially lower costs, lower incidence of peripheral neuropathy and hepatotoxicity favor the use of GC, whereas a lower incidence of hematological toxicities, and potential ease of administration in patients with borderline renal and cardiac functions favor GO. Abstract : Highlight Ramaswamy and colleagues conducted a match‐pair analysis of 326 patients with advanced gallbladder cancer treated in a real‐world setting with gemcitabine‐cisplatin versus gemcitabine‐oxaliplatin. Median event‐free survival was higher, but with marginal statistical significance, in the gemcitabine‐cisplatin arm. There was no statistical difference between the two arms in median overall survival.